2020
DOI: 10.1073/pnas.1907335117
|View full text |Cite
|
Sign up to set email alerts
|

CAMSAP3 facilitates basal body polarity and the formation of the central pair of microtubules in motile cilia

Abstract: Synchronized beating of cilia on multiciliated cells (MCCs) generates a directional flow of mucus across epithelia. This motility requires a “9 + 2” microtubule (MT) configuration in axonemes and the unidirectional array of basal bodies of cilia on the MCCs. However, it is not fully understood what components are needed for central MT-pair assembly as they are not continuous with basal bodies in contrast to the nine outer MT doublets. In this study, we discovered that a homozygous knockdown mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 55 publications
(79 reference statements)
2
36
3
Order By: Relevance
“…We found that CAMSAP3, a non-centrosomal microtubule minus-end binding protein, localizes to the base of the cilia of MCCs, in addition to γ-tubulin, a centrosomal microtubule minus-end binding protein (Clare et al, 2014). The localization of CAMSAP3 to BB of the trachea was also recently reported (Robinson et al, 2020). In contrast to the prevailing view that a connection of microtubules to a BF controls cilia orientation, we found that CAMSAP3 was not localized to BF.…”
Section: Microtubule Network and The Regulation Of Cilia Orientationcontrasting
confidence: 53%
“…We found that CAMSAP3, a non-centrosomal microtubule minus-end binding protein, localizes to the base of the cilia of MCCs, in addition to γ-tubulin, a centrosomal microtubule minus-end binding protein (Clare et al, 2014). The localization of CAMSAP3 to BB of the trachea was also recently reported (Robinson et al, 2020). In contrast to the prevailing view that a connection of microtubules to a BF controls cilia orientation, we found that CAMSAP3 was not localized to BF.…”
Section: Microtubule Network and The Regulation Of Cilia Orientationcontrasting
confidence: 53%
“…In the case of Camsap3 mutation, formation of primary cilia seemed to be unaffected. A recent study showed that loss of CAMSAP3 in nasal multi-ciliated epithelial cells affected the formation of the central pairs of microtubules in the axoneme, causing aberrant motility in motile cilia 49 . Although the primary cilia on epithelial cells are nonmotile and lack the central pairs of microtubules 50 , it remains uncertain whether the primary cilium in the Camsap3 mutant mice is still functional.…”
Section: Discussionmentioning
confidence: 99%
“…To begin investigating how CAMSAP3 contributes to microtubule assembly in axonemes, we observed its distribution in airway epithelial cells of adult trachea by immunofluorescence (IF) microscopy, using samples fixed with paraformaldehyde (PFA). The results showed that CAMSAP3 was concentrated around the apical plasma membranes (Figure 3A), as assessed by co-immunostaining for EZRIN, which is known to associate with the apical membranes or microvilli (Berryman et al, 1993), as observed in other epithelial cells (Toya et al, 2016;Robinson et al, 2020;Kimura et al, 2021;Usami et al, 2021). This position of CAMSAP3 corresponded to the proximal edge of strong a-tubulin IF signals that should represent ciliary microtubules (Figure 3B).…”
Section: Concentration Of Camsap3 Around the Proximal Ends Of Ciliamentioning
confidence: 63%
“…Whichever the case is, the CAMSAP3 dot in P30 nasal cilia may correspond to the #2 or #3 puncta in tracheal cilia, considering their distance from gtubulin of the BB. In nasal motile cilia, an additional dot overlapping with g-tubulin was also observed in P3 mice (Robinson et al, 2020), but we did not examine tracheal motile cilia in such young mice.…”
Section: Discussionmentioning
confidence: 95%